2014
DOI: 10.1016/j.joca.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Proximal femur shape differs between subjects with lateral and medial knee osteoarthritis and controls: the Osteoarthritis Initiative

Abstract: Objective This study examined the association of proximal femur shape with ipsilateral medial and lateral compartment knee OA. Design Radiographs were obtained from the NIH-funded Osteoarthritis Initiative. Cases of isolated radiographic lateral compartment knee OA were defined on baseline radiographs as Kellgren/Lawrence (K/L) Grade > = 2 and joint space narrowing (JSN) > 0 in the lateral compartment and JSN=0 in the medial compartment; isolated medial compartment knee OA had K/L ≥ 2 and JSN > 0 medially wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
2
19
0
1
Order By: Relevance
“…Our findings for the ipsilateral hip shape-knee rOA association are supported by a study of the Osteoarthritis Initiative cohort that reported an association between prevalent knee OA (lateral and medial compartments) with ipsilateral proximal femur shapes (15). In our study, Mode 2 reflects differences in the width of the femoral neck and size of the trochanters, while mode 3 is suggestive of variation in the width of the greater trochanter and femoral neck length (6).…”
Section: Discussionsupporting
confidence: 85%
“…Our findings for the ipsilateral hip shape-knee rOA association are supported by a study of the Osteoarthritis Initiative cohort that reported an association between prevalent knee OA (lateral and medial compartments) with ipsilateral proximal femur shapes (15). In our study, Mode 2 reflects differences in the width of the femoral neck and size of the trochanters, while mode 3 is suggestive of variation in the width of the greater trochanter and femoral neck length (6).…”
Section: Discussionsupporting
confidence: 85%
“…The SSM methods used in this study are similar to methods described in previous publications (10). Radiographs where the edge of the knee extended beyond the border of the radiograph or where penetration was so poor that the edge of the knee could not be identified were eliminated because a complete shape could not be defined.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported that several specific proximal femoral shapes, assessed by statistical shape modeling (SSM), are associated with incident radiographic hip OA in elderly women (9) and that proximal femoral shapes are associated with compartment-specific knee OA (10). Others have also reported that SSM-based knee shape is associated with severity of radiographic knee OA (11).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas links between different regions have been observed in disorders such as osteoarthritis (for example between hip shape and knee osteoarthritis in the study of osteoporotic fractures and the Johnston County studies; Wise et al. ; Nelson et al. ), and knee and lumbar spine in the Chingford study (Hassett et al.…”
Section: Introductionmentioning
confidence: 99%